Nitrogen-rich porous carbon derived from biomass as a high performance anode material for lithium ion batteries - Ou, Junke; Zhang, Yongzhi; Chen, Li; Zhao, Qian; Meng, Yan; Guo, Yong; Xiao, Dan (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
Nitrogen-rich porous carbon derived from ox horns has been successfully synthesized through an economically viable and an environmentally benign approach. Such an ox horn derived carbon (OHC) possesses a large surface area (BET surface area is 1300 m 2 g −1 ), a unique 3D porous nanostructure and a high inherent nitrogen content (5.5%). The OHC, as an anode material for lithium ion batteries (LIBs), exhibits superior electrochemical performances, such as a high reversible capacity (1181 mA h g −1 at a current density of 100 mA g −1 ) and a superior rate capability (304 mA h g −1 at 5 A g −1 ). Furthermore, this study demonstrates the exploitation of a universal material in nature, viz. , ox horn, as a potential anode for the most sought after energy storage application.